An Analysis of Fiscal and Monetary Policy on Private Investment: Case study of Lao. PDR - PHOUNNALY , Phayvanh; VATTHANA, Mongkhoun (Souphanouvong University Journal Multidisciplinary Research and Development, 2019)
Private investments has played significant role to Lao economic when Lao government Implementation fiscal and monetary policies that encourage private investment in Laos. The government believes that this application would graduate Laos from least developed country within 2020 and become middle-income country in 2030. Since the Asian crisis in 1998, Lao government has legislated financial and monetary policies to improve and stabilize Lao economy constantly. Lao fiscal and monetary policies analysis is, so that, important in terms of economic development in the future. This is quantitative analysis that employ secondary data from 1988-2018. It builds Econometrics model and Estimate the Ordinary Least Squares regression method. The result of the study of private investment structure in Lao PDR releases that the majority of the investment segments is foreigner investors. The private investment structure segment in GDP from 1988-2018 could cover 17% on average. This figure can infer that private investment has high positive impact to Lao economic growth. An analysis shows that the impact of financial and monetary policies on private investment is from GDP. It means launching the monetary policy to stabilize the economy by using GNP as variable has increase the private investment. On the contrary, the investment would decrease if monetary volume is used as variable. If currency exchange rate is used, the investment would fall. The result also shows that monetary policy on inflation rate, interest loan rate and budgetary deficit have no impact on private investment.